Perceptions of the Greek public on the revolutionary vision of Philip Morris International towards a smoke free-future - Doukas, Anastasios (2019)
Tobacco is the only consumer product which kills approximately half of its regular users. Therefore, traditionally, tobacco companies, were always addressed with scepticism and suspicion when undertaking corporate social responsibility activities. Recently, Philip Morris International developed a portfolio of revolutionary products in order to transform its business and deliver, what the company has labelled as, a smoke-free future with no cigarettes, placing corporate social responsibility at the center of its main business strategy. According to the company, the motivation behind this transformation is the expectation from society for them to act responsibly. After, identifying literature’s gaps this study focused on examining the perceptions of the public in regards to the flagship of the smoke-free products, the IQOS, and the company’s smoke-free vision. To answer this research question, a survey was conducted. Data from 106 responses were collected and analysed using IBM’s SPSS statistical package. The analysis of the results revealed quite high purchasing intentions for IQOS. In addition, the Greek public considers IQOS to be safer than cigarettes. Furthermore, the majority of the respondents expressed that the vision is of primary importance and that the company took a lot of effort to be socially responsible, however the trust in the vision is lower. Overall, this paper is considered to provide an insight on how the Greek public perceives the smoke-free vision and the IQOS product by Philip Morris International.